Automated warehouse systems: Finding blanks - Montemurri, David (2024)
E-commerce companies are facing a challenge in terms of customer service experience: faster and more frequent deliveries. Therefore, order picking productivity becomes a critical factor to establish a competitive advantage and, as a consequence, automation has been increasingly incorporated into warehouse systems, primarily to help order pickers improve process performance. However, new automated picking systems have not yet been extensively addressed or have received little attention from academia.This project addresses the problem by researching automated configurations and, as its main contribution, offers a new proposal to categorize these systems. Additionally, a list of relevant topics for further study is provided for researchers interested in the subject. Finally, a focus on Robotic Fulfillment Mobile Systems (RFMS) is presented to understand a very complex problem to optimize and to define a baseline configuration to serve as a parameter for future research.